A simulation model for the management and expansion of extended port terminal operations. (February 2017) - Cimpeanu, Radu; Devine, Mel T.; O'Brien, Conor
Highlights: We propose a modelling and simulation platform for the study of portuary systems. Novel features such as material unloading, transport and storage are analysed. An additional unloading facility is identified as the best long-term investment option. We assess the impact of several maintenance policies on key performance indicators. The proposed global strategy leads to an operational cost reduction of more than 85%. Abstract: This study introduces a discrete event simulation model for the analysis of bulk carrier unloading and material transport, storage and discharge at Europe's largest alumina refinery, RUSAL Aughinish Alumina. With novel features such as the integration of additional unloading functionality, auxiliary infrastructure units, as well as efficient maintenance scheduling into the material processing chain, the model is used to predict and evaluate the performance gain in the port system in the context of long-term investment and planning scenarios. Promising strategic directions in terms of large scale performance indicators such as berth occupancy and costs have been identified.